Harriet Tubman - Mara, Wil. (New York : Children's Press, 2002)
An introduction to the life and work of Harriet Tubman, who helped free slaves through the Underground Railroad and continued helping freed slaves after the Civil War.
Includes index.
3.8
K-3
Keywords: Tubman, Harriet, -- 1820?-1913 -- Juvenile literature; Slaves -- United States -- Biography -- Juvenile literature; African American women -- Biography -- Juvenile literature; African Americans -- Biography -- Juvenile literature; Underground railroad -- Juvenile literature; Tubman, Harriet, -- 1820?-1913.; Slaves; African Americans -- Biography; Women -- Biography; Underground railroad; Antislavery movements; Tubman, Harriet, -- 1820?-1913.; Slaves -- Biography; African Americans -- Biography; Women -- Biography; Underground railroad; Antislavery movements